Social engagement revealed by gaze following in third-party observers of simulated social conflict - Champ, Tess M.; Lee, SeungHyun; Martin, Anne B.; Bolles, Cameron M.; Kim, Sun Woo; Gothard, Katalin M. (Frontiers in Psychology, 2022)
Humans and non-human primates can allocate visual attention to areas of high interest in their visual field based on the behaviors of their social partners. Allocation of attention is particularly important for third-party observers of social interactions. By following the gaze of interacting individuals, the observer can obtain information about the mental states, emotions, and intentions of others. We presented three adult monkeys (Macaca mulatta) with videos of simulated social interactions and quantified their eye movements to determine which observed behaviors were most conducive to gaze following. Social interactions were simulated by juxtaposing two videos depicting a threatening and an appeasing individual facing each other, with the timing of the facial and bodily displays adjusted to mimic an exchange of social signals. Socially meaningful facial displays combined with full body movements significantly enhanced the probability of gaze following and joint attention. Despite the synthetic nature of these interactions, the facial and bodily displays of the submissive individual elicited significantly more joint-attention than gaze-following saccades, suggesting a preferential allocation of attention to the recipients of threatening displays. Temporal alignment of gaze following and joint attention to the frames of each video showed numerous clusters of significant increases in the frequency of these saccades. These clusters suggest that some videos contained signals that can induce a quasi-automatic redirection of the observer’s attention. However, these saccades occurred only on a fraction of the viewings, and we have documented large inter-individual variations. All viewers produced sequences of joint attention saccades (check backs) shifting their attention between the two monkeys as though monitoring the simulated emitting-receiving cycle of social signals. These sequences reflect the viewer's interest in monitoring the ongoing exchange of agonistic and affiliative displays. It appears that in macaque monkeys, the scanpaths of third-party observers of simulated social interactions are informed by social-cognitive processes suggestive of mentalizing.